2013
DOI: 10.1155/2013/563217
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Coagulation and Fibrinolysis during Cemented Total Hip Arthroplasty with Pre- versus Postoperative Start of Thromboprophylaxis

Abstract: Venous thrombosis is common in elective hip surgery, and prophylaxis is recommended. Clinical trials suggest that the drug dose and timing of initiating prophylaxis significantly influence antithrombotic effectiveness and safety. We studied the time course and gradient of plasma coagulation and fibrinolysis during total hip arthroplasty (THA) in twenty patients that were randomly assigned to have the first dose of 5000 IU dalteparin subcutaneously (sc) injected 12 hours before or 6 hours after surgery. Baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…[ 1 2 ] Recent studies suggested that prolonged fibrinolytic activity from delayed activation of plasmin beyond the initial surgical trauma might be a potential cause for HBL. [ 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 ] Recent studies suggested that prolonged fibrinolytic activity from delayed activation of plasmin beyond the initial surgical trauma might be a potential cause for HBL. [ 3 4 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…2009, Borgen et al. 2013). In Europe the LMWH prophylaxis has traditionally started before hip fracture surgery (Ettema et al.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after this period, the activity of t-PA decreases during a fibrinolytic shutdown phase due to a release of tissue plasminogen activator inhibitor-I (t-PAI), an acute phase reactant that naturally limits fibrinolysis. [34,37,66,67] Thus, the use of TXA can be utilized preoperatively or within the early intraoperative phase to combat the enhanced release of t-PA during surgery. TXA administered more than 24 hours post-surgery may cause over-inhibition of fibrinolytic activity due to the combined effects of TXA and t-PAI, possibly resulting in vaso-occlusive events (VOE) such as deep vein thrombosis (DVT) and pulmonary embolism (PE).…”
Section: Discussionmentioning
confidence: 99%